A novel HVDC circuit breaker for HVDC application. (July 2019) - Zhou, Meng; Xiang, Wang; Zuo, Wenping; Lin, Weixing; Wen, Jinyu
Abstract: Hybrid high voltage direct current circuit breakers (DCCBs) are capable of interrupting fault current within a few milliseconds, but this technology has high capital cost, especially in a meshed HVDC grid. To increase the economic competitiveness of hybrid DCCBs, this paper proposes a capacitor commutated dc circuit breaker (CCCB). The CCCB mainly comprises an auxiliary branch with a fast dis-connector in series with semiconductor devices and the main branch with the series connection of a dc capacitor and diode valves. This paper provides a detailed depiction of the CCCB. The topology and operating principles are discussed. The impact of snubber circuits and stray inductances on the commutation process is analyzed. The general sizing method for the main components in the CCCB is detailed. Reclosing to transmission lines with different operating conditions is studied. Several extended topologies are proposed to further reduce the semiconductor cost and on-state operation power loss. The power loss and cost of CCCB are assessed. Extensive simulations on PSCAD/EMTDC verified the dc fault isolation and reclosing of the CCCB.